Cavitation Effect towards Graphene Oxide Synthesis Using Liquid Phase Exfoliation Method Assisted by Linear Alkylbenzene Sulfonate - Susanto, Duwi; Husna, Salsabila; Dwandaru, Wipsar Sunu Brams (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
In this study, graphene oxide was synthesized using the liquid phase exfoliation method. Graphene oxide synthesis was carried out by dispersing graphite powder in deionized water and adding linear alkylbenzene sulfonate surfactant, followed by exposure to ultrasonic waves at a frequency of 21 kHz. The graphite exfoliation process in this method took advantage of the cavitation phenomenon that occurred during the sonication process. The cavitation effect in this research was observed based on the characterization results of graphene oxide. The ultraviolet-visible spectroscopy results indicated that cavitation events influenced the emergence of the main absorption peak at a wavelength of 240 nm and a secondary peak at 287 nm. The X-ray diffraction results showed a phase transition from crystalline graphite to an amorphous phase, as indicated by the disappearance of sharp graphite peaks and the appearance of broad peaks at 2θ ≅ 18°. The Fourier transform infrared analysis showed that cavitation added oxygen groups to the graphene oxide produced, e.g.: -OH and C-OH, whose intensities increased after sonication. Scanning electron microscope analysis revealed sheet-like structures on the graphite surface. Based on the energy dispersive X-ray results, the C/O ratio of the graphene oxide sample was 68.99%. This aforementioned result supported the Fourier transform infrared results where an increase in the oxygen composition occurred after the sonication.